Pengaruh Konsentrasi Jus Lidah Buaya (Aloe cbinensis Baker) Terhadap Pertumbuhan Planlet Anggrek Hasil Silangan Dendrobium Morning Sun X Dendrobium Samarai - Reo Sempana; Lia Amalia; Wahyono Widodo; Elly Roosma Ria; Noertjahyani Noertjahyani (Fakultas Pertanian Universitas Winaya Mukti, 2021)
This experiment aims was to study the effect of the concentration of aloe vera juice and to get the concentration of aloe vera juice which shows better growth of the number of leaves and the number of roots on the Dendrobium orchid plantlet in Hybrid-vitro results. This experiment was carried out at the Tissue Culture Laboratory, Faculty of Agriculture, Winaya Mukti University, which began in May to August 2019. The experimental design was used a Completely Randomized Design with 5 treatments in 5 replications and the treatments namely: A (0 g L-1 solution), B (25 g L-1 solution), C (50 g L-1 solution), D (75 g L-1 solution), E (100 g L-1 solution). The results showed that consentration of B (25 g L-1 solution), C (50 g L-1 solution), D (75 g L-1 solution) gave plantlet height, number of shoots, number of roots, and root length better than another treatments.